An Analysis of Service Quality of Robots Affecting Customers Satisfaction - Mohamad, Arifha; R. Anbarasan (Research in Management of Technology and Business, 2023)
Customer satisfaction is one of the major concern today. Covid-19 epidemic has accelerated the use of robot servers in the hospitality sector in Malaysia grows increasingly as customers are more cautious about the dangers of direct physical contact. Therefore, the intention of the study is to identify the relationship between customer satisfaction and the implication of service quality on robots within hospitality industry in Malaysia. In addition, this study uses quantitative methods by distributing questionnaires to respondents. The distribution of questionnaire to the customer in Malaysia as respondent for this study. Based on Krejcie & Morgan sample size table, 384 respondents should be involved in this study. The Statistical Packages for Social Science (SPSS) software is being utilized in this study to analyze the data obtained. The analysis consists of descriptive analysis and correlation analysis. This research will give a new perspective towards the current business world. As of that, governments can take this study as a fundamental to encourage and implement more of the of service robots in the hospitality industry throughout Malaysia.